On q-integrals over order polytopes (extended abstract) - Jang Soo Kim (Discrete Mathematics & Theoretical Computer Science, 2020)
A q-integral over an order polytope coming from a poset is interpreted as a generating function of linear extensions of the poset. As an application, theq-beta integral and aq-analog of Dirichlet’s integral are computed. A combinatorial interpretation of aq-Selberg integral is also obtained.